Objektivna politična odgovornost ministra - Cerar, Miro (Teorija in praksa, 1998)
Ministerial objective political responsibility represents a special form of responsibility, asserted separately or in connection with judicial, moral and other responsibilities. Ministerial political responsibility can be subjective or objective.The article deals with various criteria for establishing ministerial objective responsibility. There are listed some doubts regarding its assertion. However, it is stated that despite various theoretical and practical doubts, the ministerial objective political responsibility in contemporary democratic context is reasonable and grounded.
Keywords: ministri; politična odgovornost; objektivna odgovornost